Espectrometria de massa de compostos heterociclicos derivados do furano e do benzo/B/tiofeno : pirolise da nafto/2,1-b/furanodiona-1,2 - Koike, Luzia, 1946-2023 (1977)
Orientador : Luiz G. Bravo Navarrete